2019
DOI: 10.1093/ehjcr/ytz133
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy to reduce mitral regurgitation in Libman–Sacks endocarditis: a case report

Abstract: Background Libman–Sacks endocarditis is a cardiac manifestation of systemic lupus erythematosus (SLE) and is characterized by non-bacterial verrucous vegetations, causing valvular stenosis and/or regurgitation. The effectiveness of immunosuppressive therapy for valve dysfunction due to Libman–Sacks endocarditis has not been reported. Case summary A 67-year-old woman with a history of chronic atrial fibrillation was emergently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…It may present as infective endocarditis with symptoms of heart failure due to valvular regurgitation and thromboembolic events [6]. LSE is typically situated in the tip, middle, or the base of the posterior mitral leaflets and this can be confused with infective endocarditis vegetation [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may present as infective endocarditis with symptoms of heart failure due to valvular regurgitation and thromboembolic events [6]. LSE is typically situated in the tip, middle, or the base of the posterior mitral leaflets and this can be confused with infective endocarditis vegetation [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A high index of suspicion for LSE in the presence of multiorgan disease is warranted as early recognition of LSE could have an impact on its management and reduce morbidity and mortality [ 8 ]. According to pathology reports from valvular specimens, the underlying mechanism for LSE showed evidence of inflammation and cell degeneration with fibrin deposition [ 10 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiphospholipid syndrome is a non-inflammatory systemic autoimmune disease with an incidence of five new cases/100,000 persons per year and a prevalence of 40–50 cases/100,000 persons ( 3 ) and is more common in young women ( 4 ). “Definite” APS must have recurrent arteriovenous thrombosis and/or morbid pregnancy (habitual abortion, or stillbirth in the middle and late stages) as its main clinical manifestations ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study of 232 SLE patients treated with hydroxychloroquine, chloroquine, or both for a median of 52 months, a significant protective effect against thrombosis was demonstrated (HR 0.28, 95% CI 0.08–0.90) [ 31 ]. Finally, few isolated case reports have shown that immunosuppressive therapy combined with anti-thrombotic and hydroxychloroquine therapy resolve or improve Libman-Sacks endocarditis and its associated CVD [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%